2019
DOI: 10.1590/1413-7054201943017119
|View full text |Cite
|
Sign up to set email alerts
|

Potential utilization of spent Agaricus bisporus mushroom substrate for seedling production and organic fertilizer in tomato cultivation

Abstract: The production of Agaricus bisporus results in significant residual material after cultivation. Due to its physical properties and nutrient content Spent Mushroom Substrate (SMS) has great potential for use in agriculture. Our study evaluated the feasibility of using SMS as an alternative substrate for the production of Paronset® hybrid tomato seedlings and as an organic fertilizer in its production. To conduct the fruit production experiment, the plots consisted of three types of fertilizers (SMS of A. bispor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 17 publications
(15 reference statements)
2
3
0
Order By: Relevance
“…The present results are in agreement with some previous studies, which indicate the viability of using MC as an organic fertilizer for growing tomato plants [67][68][69]. Similarly, Pant and Singh, et al [59] reported that spent compost of P. sajor caju was effective for improving tomato growth parameters and soil fertility.…”
Section: Vegetative Growth Parameterssupporting
confidence: 92%
See 1 more Smart Citation
“…The present results are in agreement with some previous studies, which indicate the viability of using MC as an organic fertilizer for growing tomato plants [67][68][69]. Similarly, Pant and Singh, et al [59] reported that spent compost of P. sajor caju was effective for improving tomato growth parameters and soil fertility.…”
Section: Vegetative Growth Parameterssupporting
confidence: 92%
“…Whereas, the signi icantly lowest value of fruit yield/plant was recorded with the untreated plant in both seasons. Many authors greatly supported our indings [19,26,59,69]. They found that MC was effective as soil amendments for improving tomato growth performance and fruit yield.…”
Section: Fruit Number and Yieldsupporting
confidence: 57%
“…The results of this treatment are not reported because such effects culminated in plant death. Agaricus bisporus substrate had a similar effect on tomato seedlings, causing a 2-day delay in germination (Collela et al 2019).…”
Section: Discussionmentioning
confidence: 98%
“…The sensitivity of the vegetable crop can be determinant for the response of the crop to the substrate used, Collela et al [30] used SPCH-St as a seedling substrate and obtained vigorous and quality tomato seedlings as in the commercial substrates tested. Also the use of SPCH mixed with anaerobic digestion residues produced good results in vegetable seedlings for tomato and bell pepper [31] .…”
Section: Effect Of the Different Treatments On Germination And Seedli...mentioning
confidence: 99%